Proprier som opslagsord – kriterier for almenordbøger - Úlfarsdóttir, Þórdís (LexicoNordica, 2019)
Normally, names have not got much attention in lexicography, where their selection very much depends upon the vision of each author or editor. Proper names can be divided into several categories: 1. personal names, 2. names of historical figures, famous people etc, 3. place names, 4. named entities such as institutions, trademarks, pop groups etc. Different criteria may apply to each category of names regarding their treatment in dictionary articles. There may be a great difference in the sort of information the dictionary provides depending on its type, i.e. whether it is a monolingual or bilingual dictionary, an online dictionary or a printed book. Here it is argued that proper names should have a place in the lemma list of general language dictionaries, given that some basic criteria are met.